Bus Terminal Design in Transit Oriented Development Area (TOD) in Pinang Baris - Achmad Delianur Nasution; Rochmad Siddhiqie (Talenta Publisher, 2018)
According to the development plan of MEBIDANG-RO, Pinang Baris has been stated as TOD Area. Bus Terminal will be the transit center within the area and have direct integration to buildings surround it. Issues that appeared solved with utilizing the land that will be allocated as circulation area to prevent crossing circulation between transportation and passengers, contemporary architecture theme will be applied, and the building shape will be following the circulation plan that has made before, Therefore, the design of Pinang Baris Bus Terminal would fulfill the needs of users in TOD Pinang Baris.